The sustainability of electricity sector during Covid-19 outbreak in Malaysia - Mohd Sam, Mohd Fazli; Ismail, Albert Feisal @ Muhd Feisal; Abdul Malek, Muhammad Uzair; Suprapto, Budi (ASR Research India, 2022)
This empirical study the relationship between risk management, security supply, financial flow and technology acceleration with sustainability of the business of TNB Malaysia. The study utilised a sample of 107 staff of TNB in Brickfields, Kuala Lumpur. The independent variable risk management, security supply, financial flow and technology acceleration while the dependent variables, is measured by sustainability of the business. The conceptual framework was proposed and the hypotheses of this study were developed. Besides, the multiple regression analysis was used in analysing the data collected in this study. The finding of the study showed that risk management, security supply, financial flow, technology acceleration and sustainability of the business have a high level. Analysis also shows that there is a positive relationship between risk management, technology acceleration and security supply and financial flow with sustainability of the business. The study concluded that it provides a useful insight to different users, the pandemic is accelerating many trends and companies need to adopt new norms for the business sustainability in the future.